2020
DOI: 10.3390/jcm9124041
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of The Regulatory Region of the ITGAM Gene (-323G>A) as a Novel Predictor of a Poor Nutritional Status in Head and Neck Cancer Patients Subjected to Intensity-Modulated Radiation Therapy

Abstract: Background: The most serious disturbance of the nutritional status is neoplastic cachexia. The main factor contributing to the development of cachexia is the ongoing inflammatory process. The gene associated with the development of the inflammatory response is ITGAM. Therefore, the aim of the study was to assess the relationship between a single nucleotide polymorphism (SNP)-323G>A of the ITGAM gene and the occurrence of nutritional disorders in patients undergoing radiotherapy (RT) due to head and neck can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Survival analysis revealed that only ITGAM was significantly associated with poor NSCLC patient prognosis, with elevated ITGAM expression correlating with poorer DFS. ITGAM, or CD11b, is involved in regulating macrophage polarization, proinflammatory macrophage transcription, and immune responses ( 40 , 41 , 42 ). Recent findings indicate that ITGAM modulates angiogenesis through cytokine expression control in murine and human cancer models ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Survival analysis revealed that only ITGAM was significantly associated with poor NSCLC patient prognosis, with elevated ITGAM expression correlating with poorer DFS. ITGAM, or CD11b, is involved in regulating macrophage polarization, proinflammatory macrophage transcription, and immune responses ( 40 , 41 , 42 ). Recent findings indicate that ITGAM modulates angiogenesis through cytokine expression control in murine and human cancer models ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lei Dou et al found that the increased CCT3 can enhance cervical cancer progression through FN1 54 . ITGAM was identified as a novel predictor of oral cancer under radiation therapy 55 . Erik Laurini identified that Rad51 is involved in DNA repair and it further regulates the development of cancer 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The studies that are being available concentrate mainly on ITGAM SNPs’ role in rheumatologic conditions—mainly SLE and lupus nephritis (LN) 6 , 20 , 21 . In our recently published paper, it has been demonstrated that the investigated ITGAM SNP (-323G > A) may serve as a useful marker in the assessment of the risk of occurrence of nutritional disorders in head and neck cancer (HNC) patients undergoing radiotherapy (RT) 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The Real-Time polymerase chain reaction (PCR) technique was used for genotyping reaction on StepOnePlus device (Applied Biosystems, Foster City, CA, USA) in accordance with the manufacturer’s instructions (using Genotyping Master Mix and TaqMan probes specific for ITGAM SNP: rs7193943) (Thermo Fisher Scientific, USA). The above methods were also described in detail in our previous studies 11 14 .…”
Section: Methodsmentioning
confidence: 99%